2017
DOI: 10.24247/ijmperdjun201724
|View full text |Cite
|
Sign up to set email alerts
|

Slurry Erosive Wear Behavior of AA 6063/Tic Particles in Situ Composites

Abstract: The In-situ composite of metal matrix AA6063-xTiC (x = 0 wt. %, 3wt. %, 6 wt. %, 9 wt. %) were mixed with particulates of Tic, were synthesized by the reaction of K 2 TiF 6 and graphite with aluminum melt at 1000°C. These composites were heat treated differently to form various sets like solution zed and solution zed-aged, where they were compared with as-cast composites for erosive wear performance by testing pot type slurry-erosive wear device, respectively. This study showed an increase in wear resistance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Te authors found the wear rate of the Al/BN nanocomposite to lessen as the sliding speed was increased (from 80 to 180 mm/s) [38]. Researchers [39] analyzed a varied wear behavior for the Al alloy under minimal load and variable sliding speed, in contrast to the literature above investigations. A higher wear rate was seen up to a sliding speed of 0.1 mm/s, after which it was observed to decrease.…”
Section: Wear Test and Hardness Resultsmentioning
confidence: 99%
“…Te authors found the wear rate of the Al/BN nanocomposite to lessen as the sliding speed was increased (from 80 to 180 mm/s) [38]. Researchers [39] analyzed a varied wear behavior for the Al alloy under minimal load and variable sliding speed, in contrast to the literature above investigations. A higher wear rate was seen up to a sliding speed of 0.1 mm/s, after which it was observed to decrease.…”
Section: Wear Test and Hardness Resultsmentioning
confidence: 99%